2011
DOI: 10.1371/journal.pmed.1001092
|View full text |Cite
|
Sign up to set email alerts
|

IL28B, HLA-C, and KIR Variants Additively Predict Response to Therapy in Chronic Hepatitis C Virus Infection in a European Cohort: A Cross-Sectional Study

Abstract: Vijayaprakash Suppiah and colleagues show that genotyping hepatitis C patients for the IL28B, HLA-C, and KIR genes improves the ability to predict whether or not patients will respond to antiviral treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 35 publications
2
88
0
Order By: Relevance
“…Conversely, susceptibility factors appear to increase susceptibility. This was found in an Irish cohort, but not a larger international study 20, 21. Similarly, considering viral genotype and the response to IFN‐based therapy, IFN‐λ3/4 and centromeric A KIR haplotypes are important for treatment‐induced resolution of patients infected with HCV G1, whereas the KIR2DL3 and HLA‐class I combination, but not IFN‐λ3/4, plays a dominant role in resolving HCV G2 and G3 infection.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Conversely, susceptibility factors appear to increase susceptibility. This was found in an Irish cohort, but not a larger international study 20, 21. Similarly, considering viral genotype and the response to IFN‐based therapy, IFN‐λ3/4 and centromeric A KIR haplotypes are important for treatment‐induced resolution of patients infected with HCV G1, whereas the KIR2DL3 and HLA‐class I combination, but not IFN‐λ3/4, plays a dominant role in resolving HCV G2 and G3 infection.…”
Section: Discussionmentioning
confidence: 83%
“…In these studies it has been shown that for the SNPs associated with worse outcomes, KIR2DS3, HLA‐C2C2 and IFN‐λ3/4 (rs8099917 G allele and rs12979860 T allele), there appeared to be an interaction, as individuals with two susceptibility factors had significantly worse outcomes than those with only one 20, 21. Conversely no predictive benefit was found on combining the favorable IFN‐λ3/4 polymorphism with KIR2DL3:HLA‐C1 homozygosity for protection against viremia in seronegative exposed groups 12.…”
Section: Introductionmentioning
confidence: 99%
“…In a later Irish study, the authors found that CCR5-∆32 was significantly associated with increased spontaneous CCR5-∆32 and IL28B polymorphisms in treatment of HCV infection 14 . Importantly, this effect seemed to be due to an interaction of CCR5-∆32 with the recently described IL28B rs12979860 polymorphism, which has also been shown to influence spontaneous recovery from HCV infection 15,16 . As IL28B polymorphisms are currently the strongest host genetic markers to predict treatmentinduced clearance of HCV infection [17][18][19][20] , we designed this study to examine for a possible interaction between the CCR5-∆32 mutation and the two most predictive IL28B polymorphisms, rs8099917 and rs12979860, with respect to treatment-induced clearance of HCV infection.…”
Section: Introductionmentioning
confidence: 93%
“…Written informed consent was obtained from all participants. Characteristics of the study cohorts have been described elsewhere 16 . Briefly, all treated patients were Caucasian and infected with genotype 1, the majority of these patients received pegylated interferon and ribavirin and had virological response determined 6 months after completion of therapy.…”
Section: Ethical Approval Was Obtained From the Human Research Ethicsmentioning
confidence: 99%
“…This association is attributed to differential natural killer (NK) cell activation and function in the context of this KIR/HLA interaction [104]. In a recent cross-sectional study, Suppiah et al concluded that IL28-B, HLA-C, and KIR variants additively predict response to therapy in CHC European patients [105].…”
Section: Molecular Epidemiology Of Hcv-relatedmentioning
confidence: 99%